Validity of the instrument to determine the triggers of innovation capabilities in health care organizations [Validez del instrumento para determinar los detonantes de las capacidades de innovación en las organizaciones dedicadas al cuidado de la salud] (2018)
The proposal aims to validate an instrument that accounts for the predictors of innovation capabilities in healthcare organizations. Two techniques are accepted, one of them is the Exploratory Factor Analysis (AFE), and the other, the Confirmatory Factor Analysis (AFC). The sample consisted of 200 observations obtained from the network of high complexity hospitals in Colombia during 2016 and 2017. The research shows a valid instrument from its constructs and determinants (Knowledge Management, Human Resource Managament, Organizational Capabilities, Culture, and finally those associated with the Health Care Organizations). Furthermore, the results of the Confirmatory Factorial Analysis allowed to test the theoretical model. This type of initiative is pioneer for three reasons: 1) The application of the methods to the health sector; 2) the conceptual amplitude of a large number of internal predictors of the Innovation Capabilities and 3) the existence of some descriptive studies is detected, with special attention to innovation in a general way, but the intention of the present work goes far beyond the merely prescriptive works, tries to demonstrate by means of quantitative techniques the singularities of innovation capabilities in the health sector. © 2018 Academia Nacional de Medicina. All Rights Reserved.